Intervensi Guru dalam Mengajarkan Daily Living Skills pada Anak Down Syndrome - Faizatul Fitriyah, Qonitah (Al-Athfal: Jurnal Pendidikan Anak, 2020)
Daily living skills are an ability in someone in the field of independence in the form of daily activities. Daily living skills must be instilled early on. However, children with down syndrome must have specialized interventions so that children's living skills develop well. The purpose of this study is to describe teachers' intervention in teaching daily living skills in Ceria Demangan Kindergarten. The research method used is a case study. Data collection techniques used were observation and interviews. The subjects of this study were two students who have Down syndrome. The results of this study are individual interventions conducted in the form of habituation with routine activities, spontaneous activities, and modeling techniques, homogeneous group interventions in the form of leadership and daily pickets, and heterogeneous group interventions in the form of life skills-based learning. Individual interventions and group interventions were successfully applied to improve the living skills of children with Down syndrome in Ceria Demangan Kindergarten. Effective interventions used are individual interventions in the form of habituation and heterogeneous group interventions in the form of learning daily living skills.